PENGARUH PENGGUNAAN MEDIA BIG BOOK TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL KELAS IV UPT SD NEGERI 21 BONTORAMBA KABUPATEN JENEPONTO - Paramita Sari Mita; Hj. Rosleny Babo; Fitri Yanty Muchtar (STKIP Subang, 2025)
The main problem in this study is whether implementing Big Book media can improve social studies learning outcomes in Grade IV Students of UPT SD Negeri 21 Bontoramba, Jeneponto Regency. This study aims to determine the effect of using big book media on social studies learning outcomes of grade IV students of SD Negeri 21 Bontoramba, Jeneponto Regency.This study uses a quantitative approach with a pre-experimental design research type and One Group pretest-posttest design technique. The population and sample in this study were all grade IV students totaling 15 people with details of 4 males and 11 females. Data collection techniques include pretest-posttest, observation and documentation. The data that has been collected is then analyzed using descriptive and inferential statistical analysis technique formulas.After analyzing the data, the author found that there was a significant influence on the use of big book media on the learning outcomes of fourth grade students of UPT SD Negeri 21 Bontoramba, Jeneponto Regency. This is evidenced by the results of the calculated t value obtained, which is 37.41, which is greater than the t table value, which is 2.14 on the basis of a significant 5% taken from the learning outcomes of Social Sciences (IPS) of fourth grade students of UPT SD Negeri 21 Bontoramba, Jeneponto Regency, so it can be concluded that the use of big book media on learning Social Sciences (IPS) can improve the learning outcomes of fourth grade students of UPT SD Negeri 21 Bontoramba, Jeneponto Regency.